Malaysia Airlines System Berhad: Strategies For A Chaotic And Turbulent Global Environment After The Tragedy Of September 11 - Itam, Muhammad Dahlan (2003)
The aim of this thesis paper is to trace the history of MAS, to detail the internal and external environments in which it operates in, its strengths, weaknesses, opportunities and treats and finally to recommend the strategies that it should employ to return itself to profitability levels.